Kemampuan representasi matematis siswa pada materi bilangan berdasarkan self-confidence - Nabilah Citra Amalia Ulfa; Rostina Sundayana (Institut Pendidikan Indonesia, 2022)
The low ability of students’ mathematical representation has an effect on achievement in mathematics learning. Students find it difficult to understand what is known and asked, also are still not able to find a way out in solving the questions so many students find it difficult to solve the problems given in the form of story questions. Low self-confidence is also an influence on student success because self-confidence itself is self-confidence in doing tasks and choosing good, appropriate, and effective solutions. The purpose of this study was to analyze the mathematical representation ability of number material based on self-confidence. The subjects of this study were three class VIII junior high school students who were taken randomly. The data collection techniques in this study were tests, interviews, documentation, and questionnaires. The results of this study indicate that: (1) Respondents with a high self-confidence category can solve problems on the sub-indicators of making mathematical equations or models from other representations, making image representations to clarify problems and facilitate solving, making problem situations based on the data or representations provided; (2) Respondents with moderate self-confidence and low self-confidence categories can only solve the problem in the sub-indicator to create a problem situation based on the data or representation provided. Rendahnya kemampuan representasi matematis siswa berpengaruh terhadap prestasi dalam pembelajaran matematika. Siswa sulit memahami apa yang diketahui dan ditanyakan, juga masih kurang mampu mencari jalan keluar dalam menyelesaikan soal sehingga banyak siswa yang merasa kesulitan dalam menyelesaikan permasalahan yang diberikan dalam bentuk soal cerita. Rendahnya Self-confidence juga menjadi pengaruh terhadap keberhasilan siswa karena self-confidence itu sendiri merupakan kepercayaan diri dalam melakukan tugas dan memilih cara penyelesaian yang baik, tepat dan efektif. Tujuan penelitian ini untuk menganalisis kemampuan representasi matematis pada materi bilangan berdasarkan self-confidence. Subjek penelitian ini adalah tiga orang siswa SMP kelas VIII yang diambil acak. Adapun teknik pengumpulan data dalam penelitian ini adalah tes, wawancara, dokumentasi, angket. Hasil penelitian ini menunjukkan bahwa: (1) Responden dengan kategori self-confidence tinggi dapat menyelesaikan permasalahan pada sub indikator membuat persamaan atau model matematika dari representasi lain, membuat representasi gambar untuk memperjelas masalah dan memfasilitasi penyelesaian, membuat situasi masalah berdasarkan data atau representasi yang diberikan; (2) Responden dengan kategori self-confidence sedang dan self-confidence rendah hanya dapat menyelesaikan permasalahan pada sub indikator membuat situasi masalah berdasarkan data atau representasi yang diberikan.